The Ontology of Muhammad Iqbal's Panentheism and Its Relevance to Environmental Ethics - Anam, Rifqi Khairul (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2024)
This article examines the ontology of Muhammad Iqbal's panentheism and its implications for environmental ethics, aiming to descriptively outline the existential relationships between God, humans, and nature, and to assess how Iqbal's concepts can enhance environmental ethical frameworks. The research addresses the challenge of Muslim responses to modern science, which often focus on an Islamization process that can be exclusive. Three methods were employed: Language Analytics, analyzing Iqbal's linguistic choices; a Hermeneutic Method to interpret his texts through literal, phenomenological, and essential lenses; and a Heuristic Method to uncover insights by critiquing existing perspectives. The findings reveal that Iqbal's panentheism establishes an ontological framework that underscores the interconnectedness of all existence, linking the divine, human, material, and spiritual dimensions. This paradigm fosters a dynamic universe reflecting God's ongoing creativity and promotes environmental ethics by emphasizing unity and interdependence. Iqbal’s philosophy encourages respect for the environment, sustainable practices, and an understanding of human roles as stewards of Earth, offering a holistic and spiritually profound approach to environmental ethics.